Repeatability of multinuclear interleaved acquisitions with nuclear Overhauser enhancement effect in dynamic experiments in the calf muscle at 3T. Issue 1 (9th February 2021) - Lopez Kolkovsky, Alfredo L.; Marty, Benjamin; Giacomini, Eric; Meyerspeer, Martin; Carlier, Pierre G.
Abstract : Purpose: To evaluate the repeatability of multinuclear interleaved 1 H/ 31 P NMR dynamic acquisitions in skeletal muscle and the impact of nuclear Overhauser enhancement (nOe) on the 31 P results at 3T in exercise‐recovery and ischemia‐hyperemia paradigms. Methods: A 1 H/ 31 P interleaved pulse sequence was used to measure every 2.5 s a perfusion‐weighted image, a T 2 ∗ map, a 31 P spectrum and 32 1 H spectra sensitive to deoxymyoglobin. 21 subjects performed a plantar flexion exercise and after recovery underwent an 8‐min lower leg ischemia. The procedure was repeated in visit 2 with 12 subjects. An additional exercise bout without 1 H excitation was appended to visit 1. Individual 1 H RF pulse nOe was measured at rest in every visit. Results: Repeatability scores (coefficient of variation, Bland‐Altman analysis) were similar to those found in the literature using similar mono‐nuclear acquisitions. |Pi]/[PCr], pH drop, creatine rephosphorylation rate (τPCr ), maximum perfusion, time to peak perfusion, and blood flow post‐exercise showed high reliability (intraclass correlation coefficient > 0.7), whereas hemodynamic results from reactive hyperemia showed higher repeatability. After accounting for nOe, which increased Pi and PCr signal‐to‐noise ratio by 30%, no differences in 31 P results were observed between interleaved and 31 P MRS‐only acquisitions. τPCr was unaffected by nOe. Conclusion: The method shows good repeatability for both paradigms while simultaneously providing multiple dynamic data sets on a clinical scanner. The nOe effects were accounted for on a per‐subject and per‐visit basis using a short 31 P reference scan. This multiparametric approach has a multitude of applications for the study of oxygen utilization and ATP turnover in the muscle.